2006
DOI: 10.1111/j.1365-2257.2006.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of monoclonal gammopathy of undetermined significance: a single-centre study

Abstract: Summary The main characteristic of monoclonal gammopathies (MG) is the presence of an increased amount of both electrophoretically and immunologically homogeneous immunoglobulins (M component). According to the WHO classification, monoclonal gammopathies are classified among the non-Hodgkin's lymphomas as 'plasma cell dyscrasias'. The unknown behaviour state, so-called MGUS (monoclonal gammopathy of undetermined significance), is distinguished from the malignant diseases. We investigated the frequency and feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
0
1
Order By: Relevance
“…Similar patterns of disease groups were also noted in a large hospital population study, which revealed a monoclonal protein in 10% of all patients older than 40 years. 28 That study found an overall distribution analogous to that seen in our younger pediatric population, with 67% with IgG, 18% with IgM, and 15% with an IgA gammopathy. In their review of patient history, they also noted many similar underlying conditions associated with the monoclonal protein including autoimmune diseases (rheumatoid arthritis, systemic lupus erythematosus, Sjögren syndrome, systemic sclerosis, Crohn disease, etc), solid tumors, hematologic diseases (Castleman disease, mycosis fungoides, hairy cell leukemia, Hodgkin disease, marginal zone lymphoma, follicular lymphoma, diffuse large B-cell lymphoma, and chronic lymphoid leukemia), renal diseases, liver cirrhosis, bacterial sepsis, immunemediated polyneuropathy, and myelodysplasia.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar patterns of disease groups were also noted in a large hospital population study, which revealed a monoclonal protein in 10% of all patients older than 40 years. 28 That study found an overall distribution analogous to that seen in our younger pediatric population, with 67% with IgG, 18% with IgM, and 15% with an IgA gammopathy. In their review of patient history, they also noted many similar underlying conditions associated with the monoclonal protein including autoimmune diseases (rheumatoid arthritis, systemic lupus erythematosus, Sjögren syndrome, systemic sclerosis, Crohn disease, etc), solid tumors, hematologic diseases (Castleman disease, mycosis fungoides, hairy cell leukemia, Hodgkin disease, marginal zone lymphoma, follicular lymphoma, diffuse large B-cell lymphoma, and chronic lymphoid leukemia), renal diseases, liver cirrhosis, bacterial sepsis, immunemediated polyneuropathy, and myelodysplasia.…”
Section: Discussionsupporting
confidence: 76%
“…A main difference between our study and studies conducted in the adult population was that 50% of the adult population have been found to have a malignant monoclonal gammopathy, including multiple myeloma, plasmacytoma, primary amyloidosis, and Waldenström macroglobulinemia. 28 Nevertheless, our patients are distinct from the adult cases reported by Simon et al 28 in that none of the aforementioned malignant monoclonal gammopathies (multiple myeloma, plasmacytoma, primary amyloidosis, and Waldenström macroglobulinemia) were identified in our young cohort.…”
Section: Discussioncontrasting
confidence: 55%